A case report of caesarean myomectomy in a term pregnant woman with fibroid complicating pregnancy: in a tertiary care centre - Sraddha, Allam S.; ., Kameswaramma; Manasa, Kopperla (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Uterine leiomyomas are the benign tumors arising from the muscle cells of the uterus. These are the most common tumors observed in reproductive age group and is seen in around 2% pregnant women. The effect of fibroids on the pregnancy varies according to the number, size and their location. Most of the patients are asymptomatic. Recent literature suggests myomectomy during pregnancy and caesarean section is safe in well selected cases with experienced obstetrician in a tertiary care center.